High-cycle fatigue behavior of a laser powder bed fusion additive manufactured Ti-6Al-4V titanium: Effect of pores and tested volume size. (August 2021) - Pessard, Etienne; Lavialle, Manon; Laheurte, Pascal; Didier, Paul; Brochu, Myriam
Graphical abstract: Highlights: Original fatigue results on a Ti-6Al-4V LPBF with and without pores are presented. The fatigue strength sensitivity to defect size is clearly characterized. With a small loaded volume and in the absence of pores, the fatigue strength is very high. In the absence of pores, the fatigue strength is very sensitive to the loaded volume size. The criterion proposed results in a probabilistic Kitagawa type diagram. Abstract: This work is focused on the effect of natural defect on the fatigue resistance of a laser powder bed fusion additively manufactured Ti-6Al-4V titanium. To reveal the fatigue strength variability and its sensitivity to the defect size, push-pull fatigue tests have been undertaken on specimens with different sizes of highly loaded volume of material. In order to easily vary the size of the highly loaded volume, specimens containing different numbers of surface hemispherical shape holes of 600 μ m in diameter have been tested. This method also allowed to test small volume which triggered crack initiation from microstructural features. The fatigue damage mechanisms observed and the average natural defect size measured on the failure surfaces depend on the size of the highly stressed region. A higher fatigue strength is observed for smaller stressed volumes and defect free regions. To reduce the impact lack-of-fusion on fatigue and increase the probability of triggering crack initiation from a microstructural feature, the specimens were built in the horizontal direction. For specimens where fatigue cracks initiated at natural discontinuities, the results reported in a Kitagawa-Takahashi diagram revealed a critical defect size ( area ) in the range of 30 μ m . In addition, a probabilistic approach based on the weakest link theory is proposed. The model describes a probabilistic Kitagawa-Takahashi diagram accounting for the size of both the highly stressed volume and the natural defect.